PENGARUH JOB SATISFACTION DAN PERCEIVED EASE OF MOVEMENT TERHADAP TURNOVER INTENTIONS PERAWAT - Ari Kuntardina (Universitas YPPI Rembang, 2021)
Nurses have a big role in patient care and the sustainability of a hospital. The lack of nurses affects public health services. Adequacy in the number and quality of nurses must be considered. The purpose of this study is to examine and analyze the effect of Job Satisfaction and Perceived Ease of Movement on Turnover Intentions. This research was conducted at a Class D hospital. The population was 55 nurses. The sampling technique used is saturation sampling. Data collection through questionnaires and data analysis in hypothesis testing using Pearson Product Moment Correlation Technique. The analysis shows that the Perceived Ease of Movement and Job Satisfaction affect nurses' turnover intentions. The results of this study are expected to provide input for hospital management in improving nurse Job Satisfaction in an effort to reduce nurse turnover intentions.